PENILAIAN KONDISI DAN PENANGANAN JEMBATAN DI PROVINSI SUMATERA BARAT - Eva Rita; Robbi Permata; Joko Siswoyo; Nasfryzal Carlo (Ethos: Jurnal Penelitian dan Pengabdian kepada Masyarakat, 2018)
The bridge is an important part of the road that is needed in the system of transportation network to support the developing of an area. If the bridge is not functioning properly it can disturb the traffic comfort and result in disruption of economic relations. In West Sumatera in 2012, there has been a shift in the status of regency roads to provincial strategic streets along 926.13 km and by 2015 along 466.67 km provincial strategic roads have turned into provincial roads. The existence of such road changes resulted in a bridge that also changed its status. There are 108 bridges that will decrease its stability from 91.17% to 88.14%. To improve the stability of the bridge, the condition and handling of 108 bridges should be carried out. The method used is descriptive evaluative research. The bridge condition assessment is done visually to determine the overall condition of bridge eksxisting referring to Bridge Management System (BMS) standard and with the help of Bridge Management System Information System (SIM-IBMS). To improve the condition of the bridge can be monitored and can be determined some appropriate handling measures. The results of the appraisal were 33 in good condition, 22 were lightly damaged, 18 were moderately damaged and 35 were heavily damaged. Technical Screening of the handling type obtained by 33 bridges requires routine maintenance, 22 bridges require routine maintenance and periodic maintenance, 18 bridges need rehabilitation, duplication, improvement and widening and 19 bridges require replacement and 16 bridges require construction. Skale priority for handling the bridge required a more detailed budget calculations in accordance with the conditions.